How much GK is in the NKLM? A comparison between the catalogues of exam-relevant topics (GK) and the German National Competence-based Learning Objectives Catalogue for Undergraduate Medical Education (NKLM) - Fritze, Olaf (GMS Journal for Medical Education, 2017)
Background: The German National Competence-Based Learning Objectives for Undergraduate Medical Education (NKLM) being adopted in 2015 is designed to contribute to improve the quality of teaching and learning in medicine with respect to competence orientation. For departments, the coherence between teaching, assessment and the content of the catalogues of exam-relevant topics (GK) is a crucial factor. Before making use of the NKLM seriously in curricular development, many faculties demand more transparency regarding the representation in the NKLM of GK topics and in what aspects the NKLM exceeds the GK. Therefore, the aim of the study was to assign the NKLM competencies and objectives to the systematic GK terms, to reveal gaps in their congruence and to determine the percentage of agreement between GK and NKLM. Additionally, the distribution among the NKLM chapters (chap.), of GK content and further competencies relevant for medical practice were analysed. Methods: The textual comparison of GK and NKLM was done by advanced students that were familiar with the NKLM from previous analyses. The comparison was done independently (keyword search, face validity), afterwards consented and matched with independent ratings of GK-2 and chapter 21 done by experts as well as with cross-references to the GK indicated in chapter 12, 13 and 15 of the NKLM. Detailed data is available online: . Results: The degree of correspondence of the GK’s six preclinical parts with the NKLM ranges between 94% and 98%, with the clinical GK the degree of correspondence ranging between 84% and 88%. This demonstrates a consistently very high congruence of content. Only 6-16% of the content per GK part could not be assigned to NKLM equivalents. Regarding the distribution of GK content among NKLM chapters, the chapters with classic medical expertise (chapters 12, 13, 16, 17 as well as 20 and 21) show the highest correspondences. Practical medical skills (chapter 14b) can be found in the clinical GK “Health Disorders”. Doctor-patient interaction (chapter 14c) and medical scientific skills (chapter 14a) are represented only marginally in the GK. As expected, there were no equivalents to be found in the GK for the new professional roles for medical doctors (chapter 06-11).Discussion: The results presented provide faculties with a useful and detailed data base to evaluate the NKLM more reliably, especially with respect to its relevance for exams. The increased transparency supports the implementation process of the NKLM by reducing content-related uncertainties of departments, invalidating sweeping arguments against the NKLM resulting from uncertainties and thereby minimizing resistance. At the same time a critical review process of the NKLM is encouraged.